Salvador Dalí’s Liquid and Gaseous Television: a Mystical and Wireless Dream - Anna Luigia De Simone (VIEW Journal of European Television History and Culture)
How can you reach the sky? For Salvador Dalí, just turn on your TV. That is, the Liquid and Gaseous Television: one of his inventions (1975) turning TV into a vehicle for cosmic voyages that allow man to communicate with the universe. Perhaps even with God. This device needs no wires. In it, communicative and transcendental horizons converge, updating the surrealist techniques of activating the unconscious into a new formula aimed at overturning coercive television narcosis into a liberating mystical-cognitive three-dimensional ecstasy. Dalí’s wireless TV is a mechanism of mediation between reality and spirituality, discontinuity and reconfiguration, man and the sky. A dream or a model that embodies the future of television.